2019
DOI: 10.1016/j.jvs.2019.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Total IN.PACT drug-coated balloon initiative reporting pooled imaging and propensity-matched cohorts

Abstract: Objective: Randomized controlled trials have shown that drug-coated balloons (DCBs) provide superior results compared with percutaneous transluminal angioplasty (PTA) for the treatment of femoropopliteal artery disease. However, these trials have generally included short lesions, few occlusions, and small sample sizes. The present study was an individual-level pooled analysis of duplex ultrasonography (DUS) core laboratory-adjudicated and clinical events committee-adjudicated IN.PACT Admiral DCB subjects acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Interestingly, more complex FP lesions including: (1) bilateral calcification and (2) history of stent implantation, which mean clinically challenging in achieving technical success as well as long-term success, were significantly associated with ΔRVD ≥1 mm. [14][15][16][17] Not surprisingly, presence of bi-lateral calcification would be barrier to appropriately evaluate RVD by angiography because it would disturb the assessment of vessel feature. 18 History of stent implantation might reflect long and extensive exposure to arteriosclerosis, which might be the consequence of high plaque burden and diffuse disease.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, more complex FP lesions including: (1) bilateral calcification and (2) history of stent implantation, which mean clinically challenging in achieving technical success as well as long-term success, were significantly associated with ΔRVD ≥1 mm. [14][15][16][17] Not surprisingly, presence of bi-lateral calcification would be barrier to appropriately evaluate RVD by angiography because it would disturb the assessment of vessel feature. 18 History of stent implantation might reflect long and extensive exposure to arteriosclerosis, which might be the consequence of high plaque burden and diffuse disease.…”
Section: Discussionmentioning
confidence: 99%
“…10 However, in this trial, the average lesion length was 9.2 cm PACT DCB) also identified increasing lesion length (as well as diabetes mellitus and previous iliac revascularization) as significant predictors for loss of primary patency at 12 months. 12 A recent large-scale U.S. registry analysis that aimed to assess DCB and DES trends for FP lesions found that DCBs are predominantly being deployed in medium-length lesions with minimal calcification, whereas DES are being used more frequently in long and heavily calcified lesions. 13 The REAL PTX RCT aimed to directly compare performance of the Cook Zilver PTX Drug-Eluting Peripheral Stent and DCBs with a provisional stenting strategy (primarily, the IN.PACT Admiral) in FP lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The high level of occlusion (such as suprainguinal disease) and single stage multisegmented revascularization are high risk of perioperative MACE due to rapidly decreasing of afterload and rapid increasing of blood flow to lower limbs (Figure 6) [41,42]. In addition, the new technology of the antiproliferative agent embeds endovascular device which has increased the patency of the target arterial lesion are increasing to use in CLTI patients who undergo ET [21][22][23][24][25][26]. Some cohort study and meta-analysis report the high incidence of MACE in CLTI patients after revascularization by DCB and DES.…”
Section: Mace Related To Endovascular Treatmentmentioning
confidence: 99%
“…Recently, the novel technology developed the antiproliferative agent -coated and -eluting device which can deliver the drugs to the vessel wall to limit the neointimal growth within de novo vascular system and stent [21][22][23][24][25][26]. However, some literatures report the MACE, aneurysmal degeneration, vascular fibrinoid necrosis, small vessel inflammation, and budget impact after drug technology device including drug coated balloon (DCB) and drug eluting stent (DES) in patients with ET [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%